HF-Schumann Band Non-linear Coupling in Ionosphere - Yampolski, Yu. M.; Bliokh, P. V.; Beley, V. S.; Galushko, V. G.; Kascheev, S. B. (Видавничий дім «Академперіодика», 2012)
HF-Schumann Band Non-linear Coupling in Ionosphere